Lessons on heroism in the Iliad - Ibáñez, Franklin (2020)
The Iliad explains the foundations of western moral. It is not a simple text with a linear argumentation. Several lessons may be obtained from the book. Some teachings can be seen contradictory as the appraisal for courage and force while, at the same time, it does not dismiss the proper place of compassion and forgiveness. Its hero model does not seem to be a machine of war. This paper explores several dimensions of heroism to illustrate some lessons which can be valid in nowadays.